Ethical challenges when using coercion in mental healthcare: A systematic literature review - Hem, Marit Helene (Nursing ethics, 2018)
Background:To better understand the kinds of ethical challenges that emerge when using coercion in mental healthcare, and the importance of these ethical challenges, this article presents a systematic review of scientific literature.Methods:A systematic search in the databases MEDLINE, PsychInfo, Cinahl, Sociological Abstracts and Web of Knowledge was carried out. The search terms derived from the population, intervention, comparison/setting and outcome. A total of 22 studies were included.Ethical considerations:The review is conducted according to the Vancouver Protocol.Results:There are few studies that study ethical challenges when using coercion in an explicit way. However, promoting the patient’s best interest is the most important justification for coercion. Patient autonomy is a fundamental challenge facing any use of coercion, and some kind of autonomy infringement is a key aspect of the concept of coercion. The concepts of coercion and autonomy and the relations between them are very complex. When coercion is used, a primary ethical challenge is to assess the balance between promoting good (beneficence) and inflicting harm (maleficence). In the included studies, findings explicitly related to justice are few. Some studies focus on moral distress experienced by the healthcare professionals using coercion.Conclusion:There is a lack of literature explicitly addressing ethical challenges related to the use of coercion in mental healthcare. It is essential for healthcare personnel to develop a strong awareness of which ethical challenges they face in connection with the use of coercion, as well as challenges related to justice. How to address ethical challenges in ways that prevent illegitimate paternalism and strengthen beneficent treatment and care and trust in connection with the use of coercion is a ‘clinical must’. By developing a more refined and rich language describing ethical challenges, clinicians may be better equipped to prevent coercion and the accompanying moral distress.